Hidroxipropilmetilcelulosa y carbopol en el desarrollo de tabletas de diclofenaco sódico de liberación controlada - Alva Plasencia, Pedro Marcelo (2007)
The present study is studied the application of Hydroxypropylmethylcellulose and Carbopol in the development of controlled release tablets of sodium Diclofenac. Controlled release tablets of sodium Diclofenac of 100 mg were formulated based on hydrophilic matrices, Hydroxypropylmethylcelullose METHOCELTM K15M and Carbopol 974P. Eigth formulations of Hydroxypropylmethylcelullose and Carbopol 974P tablets were designed, according to a factorial design. They were used as factors common to exicipients, Cellulose microcrystalline and Lactose. The type of dissolution kinetics (order zero, order one and Higuchi) was identified. The commercial formulations of reference were, Voltaren SR® (Novartis Laboratory) and Diclofenaco Retard (Genfar® Laboratory). The apparatus 2 of USP 29 NF 24 was used, in a dissolution medium with gradual change of pH between 1,1 and 8,8. The best dissolution kinetics was zero-order for the tablets with Hydroxypropylmethylcelullose and first order for the tablets with Carbopol 974P. The values of the dissolution rate constants for the best formulations were: Hydroxypropylmethylcelullose 130 mg, Cellulose Microcrystalline 10 mg and Lactose 40 mg; 0,192 mg/min and Carbopol 974P 180 mg, Cellulose Microcrystalline 20 mg and Lactose 60 mg; 0,009 min-1. This study demonstrated that Hydroxypropylmethylcelullose controls better than Carbopol 974P the release of sodium Diclofenaco tablets as formulated